POLICY IMPLEMENTATION EVALUATION DELEGATION OF SOME EARLY CHILD EDUCATION AUTHORITIES BECOME A VILLAGE-SCALE LOCAL AUTHORITY (STUDY IN LEBAK DISTRICT, BANTEN PROVINCE) - Rusito, Rusito (NIAGARA Scientific Journal, 2023)
The policy of delegating some PAUD authorities to local authorities at village level has been implemented. However, the achievement of the target of rough participation figures has not increased significantly. The purpose of this paper is to gain an in- epth understanding of the aspects related to the evaluation results of the implementation of policies on the implementation of local- cale village-level authority on Early Childhood Education. The framework used is thinking Edward III (1980: 10) Evaluation results on the implementation of policies on the implementation of Early Childhood Education after the delegation of several authorities to local authority on a village scale has begun to increase but still needs to be maximized. Efforts to improve Early Childhood Education still need maximum support on effective aspects of communication, adequate resources, disposition or atitudes and bureaucratic structures.